Rancang Bangun Sistem Pakar Untuk Menentukan Penyakit Mulut Dengan Menggunakan Metode Certainty Factor - Ardiyanto, Meitha Tri; Irawan, Jusak; Soebadi, Bagus (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Dentistry graduates are required to treat patients with various diseases of mouth. A dentist who examined the patient should undertake a careful and thorough examination in order to determine the disease suffered by the patient. It is not always easy for the newly graduated dentists to deal with a wide variety of oral diseases. It is urgently needed a system that is able to facilitate the new dentist in diagnosing diseases of the mouth and how to follow up the disease. Based on the description of the problems, in this work we designed a web-based expert system application. The application is expected to help to overcome the problems of dentists who just completed his studies in diagnosing and following up on the patient's natural disease. The expert system uses the certainty factor method to determine any symptoms experienced by the patient. The diagnosis is expected to produce a report to assist dentists in making a follow-up to the natural disease in the patient and save it into the database system. Based on the test results showed that the application of this expert system has the accuracy of 100% to indicate that the system is able to determine the type of oral disease. The accuracy of the results obtained from 10 test by a dentist.